Pengaruh Gaya Kepemimpinan Dan Budaya Organisasi Terhadap Disiplin Kerja Pada PT. Telkom Indonesia Cabang Tenggarong - Erwinsyah, Erwinsyah; Syahrudin, Syahrudin; Efrizal, M. Dicky (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2021)
Abstract: This study aims to determine how much influence the leadership style and organizational culture have on work discipline among employees of PT. Telkom Indonesia Tenggarong Branch. The population as well as the sample is 49 people. The analytical tool used is multiple linear regression with two independent variables, namely leadership style and organizational culture. Meanwhile, one dependent variable is work discipline. Data analysis techniques used the help of a computer application program SPSS 24. The results showed the value of the F test of 41.583, thus it can be seen that the variable leadership style and organizational culture have a simultaneous influence on work discipline at PT. Telkom Indonesia Tenggarong Branch. From the results of the t test analysis, it is known that the variable of leadership style has a partial effect on work discipline, the results of t count are 7.975> 2.012 (t table), while the variables of organizational culture have no partial effect on work discipline with t count 0.383 <2.012 ( t table). The results of the study of the variable leadership style affect work discipline. This can be compared from the variable value of leadership style (X1) 0.802 and organizational culture (X2) 0.389. Based on the results of the calculation, it can be concluded that the simultaneous influence hypothesis and leadership style variables have the most dominant influence on work discipline at PT. The Tenggarong Branch of Telkom Indonesia has been proven to be true. Keywords: Leadership Style, Organizational Culture, Work Discipline